Topology Optimization of Electrolyte-Anode Interfaces in Solid Oxide Fuel Cells. (10th July 2019) - Onishi, Junya; Shikazono, Naoki
Abstract : Topology optimization of electrolyte-anode interfaces in solid oxide fuel cells is presented. The total amount of reaction current is chosen as an objective function to be maximized. A cylindrical pillar is used as an initial condition, and the interface shape is iteratively updated using the optimization procedure based on the adjoint method. The effects of material properties, such as the ionic conductivities of the electrolyte and the anode, on the geometrical characteristics as well as the electrochemical performance of the optimal structure are investigated systematically.